2018
DOI: 10.2174/1573396314666180508121625
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Neutropenia in Children with Cancer: Approach to Diagnosis and Treatment

Abstract: The standard of care in febrile neutropenic children is that they should be hospitalized, especially if high risk, and should be treated urgently with intravenous wide spectrum empiric antibiotics, the spectrum covering P. Aeruginosa. Empiric treatment should be modified according to culture results and clinical situation. Other options for low risk patients are starting with intravenous treatment and continuing with per oral treatment or giving per oral antibiotic treatment from the beginning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 0 publications
2
30
0
9
Order By: Relevance
“…The possible reasons for this shift are better control Solid tumor cancer 6 1 2 Staphylococcus aureus (MRSA) has been noted. Gramnegative bacteremia may be relatively more frequent in lowincome settings due to the absence of central venous lines [17,18]. Similar suggestive results in studies conducted in paediatric neutropenic patients in Turkey by Celkan [19] and Sweden by Bjorkholm et al [20] reported that gram-positive organisms were more pre-dominant by 60-69%.…”
Section: Discussionmentioning
confidence: 61%
“…The possible reasons for this shift are better control Solid tumor cancer 6 1 2 Staphylococcus aureus (MRSA) has been noted. Gramnegative bacteremia may be relatively more frequent in lowincome settings due to the absence of central venous lines [17,18]. Similar suggestive results in studies conducted in paediatric neutropenic patients in Turkey by Celkan [19] and Sweden by Bjorkholm et al [20] reported that gram-positive organisms were more pre-dominant by 60-69%.…”
Section: Discussionmentioning
confidence: 61%
“…But comparative study at Bangabandhu Sheikh Mujib Medical University Hospital showed that empirical treatment of FN with combined cefepime and amikacin is more effective than combination of ceftriaxone and gentamicin in children with malignancies [14]. Empiric antibiotic therapy with agents active on viridans group Streptococci and Pseudomonas aeruginosa are recommended as a standard of care in high-risk FN childhood cancer patients to provide coverage for virulent organisms while minimizing exposure to unnecessary antibiotics, because indiscriminant use of broad-spectrum antibiotics may accelerate antibiotic resistance rates [3, 15]. β-Lactams and aminoglycosides were the most common antibiotics used in our setup.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to the EAT, combination of ceftriaxone and gentamycin constituted around 72% of the regimen in the current study. But comparative study at Bangabandhu Sheikh Mujib Medical University Hospital showed that empirical treatment of FN with combined cefepime and amikacin is more effective than combination of ceftriaxone and gentamicin in children with malignancies [14].Empiric antibiotic therapy with agents active on viridans group streptococci and pseudomonas aeruginosa are recommended as a standard of care in high-risk FN childhood cancer patients to provide coverage for virulent organisms while minimizing exposure to unnecessary antibiotics, because indiscriminant use of broad-spectrum antibiotics may accelerate antibiotic resistance rates [3,15]. β-lactams and aminoglycosides were the most common antibiotics used in our setup.…”
Section: Discussionmentioning
confidence: 99%